Study of the exclusive initial-state-radiation production of the D(D)over-bar system - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2007)
A search for charmonium and other new states is performed in a study of exclusive initial-state-radiation production of DD̄ events from electron-positron annihilations at a center-of-mass energy of 10.58 GeV. The data sample corresponds to an integrated luminosity of 384fb-1 and was recorded by the BABAR experiment at the PEP-II storage ring. The DD̄ mass spectrum shows clear evidence of the ψ(3770) plus other structures near 3.9, 4.1, and 4.4GeV/c2. No evidence for Y(4260)→DD̄ is observed, leading to an upper limit of B(Y(4260)→DD̄)/B(Y(4260)→J/ψπ+π-)<1.0 at 90% confidence level. © 2007 The American Physical Society.